EARLY DETECTION OF PREGNANT WOMEN IN EMPOWERMENT OF POSYANDU CADRES IN BONDOYUDO VILLAGE, LUMAJANG - Nurul Hayati; Sri Wahyuningsih; Musviro Musviro (UPT Penerbitan Universitas Jember, 2022)
Anemia in pregnancy is a high risk that can disrupt the development and growth of the fetus. Even these disorders follow the child's life in the future. Pregnant women with anemia are at risk of giving birth to babies with iron deficiency anemia, which may last into childhood. The purpose of this service is to provide health information about the importance of Fe tablets for pregnancy and to empower Posyandu cadres in Bondoyudo Village. As we know, anemia is a disease that can harm and even cause death in pregnant women. The method uses counseling using power point media and leaflets for posyandu cadres in Bondoyudo Village, Lumajang Regency which was held on October 27, 2022, at the home of one of the Posyandu cadres in Bondoyudo Village. The results that really support the success of this community service activity are good coordination between presenters and village officials, posyandu cadres, village midwives and nurses, and the Sukodono Health Center. Submission of material in the form of leaflets and media projectors, there were discussions and questions and answers for quite a long time, as well as door prizes for participants who dared to ask questions. Some of the inhibiting factors in this community service activity are the time and conditions during a pandemic so that the application of health protocols must remain a priority. The conclusion of this community service activity can be said to be successful. This can be observed at the level of attendance, the activeness of the participants. This activity took place in an orderly and good manner without encountering significant obstacles. Follow-up that needs to be done is to continuously provide information about anemia and how to detect anemia early in pregnant women in Bondoyudo Village, Lumajang Regency. Keywords: anemia, early detection, empowerment of cadres